HIV-1 e células germinativas humanas: possíveis vias e mecanismos de infecção - Raquel de Lima Leite Soares Alvarenga (2016)
Semen is the most important mechanism for spreading of the human immunodeficiency virus (HIV) infection in the world. The source of free viral particles and the infected cells present in the seminal fluid, as well as the nature of the interactions between HIV and other spermatozoa and spermatogenic cells are still barely known. The fact that increasing numbers of studies have described the persistence of virus in semen up to 30% of patients undergoing different combinations of antiretroviral treatments, suggests that the male genital system is an anatomical/pharmacological sanctuary that prevents the eradication of the virus in the body. In this context, it is necessary to investigate the permissiveness of spermatogenic cells to HIV, as well as the contribution of these cells to the viral load of semen. The purpose of this study was to use the culture of isolated testicular cells to study the nature of interactions between testicular germ cells and HIV-1 in vitro. It was also used the germ cell lineage derived from seminoma, the TCAM-2. These cells were analyzed for different phases of infection: viral entry, viral DNA synthesis and integration of viral protein synthesis and viral production. It was observed that the reverse transcription and integration of HIV to the TCAM-2 cells occur when the input is favored by a large tropism VSV-HIV pseudovirus and after 24 hours of exposure to chloroquine. It was also demonstrated the production of viral particles by TCAM-2 cells, however we were unable to confirm the re-infection with the virus produced. On the other hand, it was demonstrated the binding of the HIV-1 virus to testicular germ cells. The internalization of p24 particles to both TCAM-2 and testicular germ cells was evaluatedthrough the study of serial sections obtained by confocal microscopy. These results together suggest that HIV-1 can be internalized by spermatogenic cells in culture, although this is a rare event. Also, further studies have to be done in order to evaluate the subsequent events, for instance reverse transcription and integration, after the virus entrance in testicular germ cells.